A high concentration Ti3C2T x MXene colloids, methods of making and using same

CN122916145APending Publication Date: 2026-10-16NANJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611109884.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

上述方案的高浓度主要来自末端浓缩,并未在前端洗涤过程中解决用水量大、片层流失与固含量下降之间的矛盾

Benefits of technology

(1)本发明在刻蚀母液与去离子水洗涤之间设置浓度递减的盐酸洗涤步骤,可通过逐级置换沉淀中残留的高酸度刻蚀母液,预先降低体系的自由酸负荷及可溶性离子负荷,从而减少后续去离子水洗涤次数,降低反复洗涤造成的体系稀释和片层氧化风险;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916145A_ABST
    Figure CN122916145A_ABST
Patent Text Reader

Abstract

The application discloses a high-concentration Ti3C2T x MXene colloids, preparation method and application thereof. LiF and HCl solution are mixed to prepare etching solution, Ti3AlC2 is added for etching, the etching mother liquor is removed by centrifugation, and the precipitate is washed with hydrochloric acid washing solution with decreasing concentration in sequence; water is added to the precipitate, and the supernatant with pH greater than 6 and in a stable and uniform black dispersion state is reserved after vortex redispersion and centrifugation; the supernatant is subjected to cyclic vortex, centrifugation and inert atmosphere ice bath ultrasonic treatment to obtain Ti3C2T x nanosheet colloidal dispersion liquid; the upper-layer black colloidal dispersion liquids in each cycle are combined through centrifugal classification and precipitate circulation extraction to obtain Ti3C2T x MXene colloids. The application can reduce the number of water washing times and sheet layer loss, does not need end secondary concentration, has simple process and is suitable for large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of liquid-phase preparation technology of two-dimensional nanomaterials, specifically relating to a high-concentration Ti3C2T x MXene colloids, their preparation methods, and applications. Background Technology

[0002] MXenes are a class of two-dimensional layered materials composed of transition metal carbides, nitrides, or carbonitrides, with the general formula M. n+1 X n T x Where M is an early transition metal, X is carbon and / or nitrogen, and T is... x It has surface end groups such as -OH, -O, or -F. Ti3C2T x With high electrical conductivity, good hydrophilicity, abundant surface functional groups, and excellent liquid-phase processing properties, Ti3C2T shows promise for applications in energy storage, electromagnetic shielding, sensing, catalysis, and tribology. x MXene is typically obtained by selectively removing the Al layer and further exfoliating, using the Ti3AlC2MAX phase as a precursor. The LiF / HCl in-situ generation hydrofluoric acid etching system avoids the direct addition of concentrated hydrofluoric acid and can utilize Li... + Intercalation facilitates subsequent exfoliation, thus becoming a commonly used preparation route.

[0003] However, existing LiF / HCl routes typically involve adding a large amount of deionized water directly after etching, followed by repeated centrifugation and washing until the supernatant is nearly neutral. The etching mother solution has high free acidity and contains Li. + Species containing Al, F Switching directly from a high-acidity, high-ionic-strength environment to a deionized water system, along with other soluble byproducts, not only requires numerous washing cycles but also results in repeated dilution of the system. Furthermore, during direct water washing, as acidity and ionic strength rapidly decrease, some of the already loosened or detached Ti3C2T... x The MXene flakes will prematurely enter the black supernatant. If all the supernatant is discarded using conventional washing methods, the effective flakes will be lost with the washing solution; if all the early acidic supernatant is retained to avoid loss, a large amount of residual acid and soluble salts will be carried into the final colloid, increasing the burden on subsequent purification. Some existing high-concentration MXene preparation methods involve removing the supernatant by high-speed centrifugation and redispersing with a small amount of water after conventional washing and stripping, or using post-treatment such as intercalation agents or thermal evaporation to achieve concentration. The high concentration of the above methods mainly comes from the end-stage concentration and does not solve the contradiction between large water consumption, flake loss and decreased solids content during the front-end washing process.

[0004] Therefore, it is necessary to establish a method that can reduce the acidity and soluble ionic load of the etching slurry before water washing, identify the transition point between the solid phase impurity removal stage and the colloidal recovery stage during water washing, and switch the supernatant treatment method accordingly, thereby avoiding reliance on end-of-pipe secondary concentration of Ti3C2T. x Methods for preparing MXene colloids. Summary of the Invention

[0005] To overcome the problems existing in the prior art, this invention provides a high-concentration Ti3C2T based on acid loading gradient unloading and colloidal phase window switching. x MXene colloids, their preparation methods, and applications. This method does not involve evaporation, sedimentation, or flocculation concentration of low-concentration colloids at the end of the preparation process. Instead, before the etching product enters the deionized water washing process, the residual acid and soluble ion load in the system are pre-reduced using a hydrochloric acid washing solution with decreasing concentrations. Simultaneously, the supernatant treatment method is switched according to the pH and dispersion state of the washing supernatant, thereby reducing the number of washing cycles and maximizing the effective Ti3C2T content. x This reduces the loss of lamellar layers, decreases the dilution of the system, and allows for the direct acquisition of a high-concentration colloidal dispersion after peeling and fractionation.

[0006] The acid load cascade unloading described in this invention refers to setting up at least two stages of hydrochloric acid washing solutions with progressively decreasing concentrations between the high-acidity etching mother liquor treatment step and the deionized water washing step. By gradually replacing the high-acidity etching mother liquor remaining in the precipitate, the free acid load and ionic strength of the environment in which the etching product is located are gradually reduced, and soluble species containing Li, Al, or F and other etching byproducts are removed in advance before entering the water washing step.

[0007] The colloidal phase window described in this invention includes a pre-treatment stage for acid and impurity removal and a post-treatment stage for stabilizing the colloidal phase. In the initial stage of water washing, the supernatant still has high acidity and ionic strength, primarily used to remove residual acidic media and soluble byproducts. When the supernatant pH is ≤6 or does not exhibit a stable, uniform black dispersion after centrifugation, the supernatant is discarded. When the supernatant pH is >6 and still exhibits a stable, uniform black dispersion after centrifugation, the system is considered to have entered the stabilizing colloidal phase, and the supernatant is retained.

[0008] To achieve the above objectives, the present invention adopts the following technical solution:

[0009] (I) This invention provides a high-concentration Ti3C2T x The method for preparing MXene colloids includes the following steps: S1: Prepare an etching solution by mixing LiF with HCl solution, add Ti3AlC2 to the etching solution for etching, remove the mother etching solution by centrifugation, and wash the precipitate with at least two stages of dilute hydrochloric acid solution with concentrations from high to low. S2: Add deionized water to the precipitate obtained in step S1, and perform vortex redispersion and centrifugation treatment in sequence, repeating at least once; if the pH of the supernatant is ≤6 or it does not show a stable and uniform black dispersion state after centrifugation, discard the supernatant; if the pH of the supernatant is >6 and it still shows a stable and uniform black dispersion state after centrifugation, retain the supernatant to obtain a black dispersion. S3: The black dispersion obtained in step S2 is subjected to multiple rounds of vortexing and centrifugation, followed by ultrasonic treatment under an inert atmosphere and ice bath conditions to obtain Ti3C2T. x Nanosheet colloidal dispersion; S4: Take the Ti3C2T obtained in step S3 x The nanosheet colloidal dispersion was centrifuged, and the upper black colloidal dispersion was collected. The resulting precipitate was redispersed with water by vortexing and centrifugation again, and the upper black colloidal dispersion was collected. The process of redispersing the precipitate with water, centrifugation, and collecting the upper black colloidal dispersion was repeated, and the upper black colloidal dispersions obtained from each round were combined to obtain Ti3C2T. x MXene colloidal dispersion.

[0010] Further, in step S1, the etching mother solution is removed by centrifugation, and the precipitate is washed sequentially with a first hydrochloric acid washing solution and a second hydrochloric acid washing solution with a concentration lower than that of the first hydrochloric acid washing solution. The first hydrochloric acid washing solution and the second hydrochloric acid washing solution are washed 1 to 2 times respectively. The concentration of the first hydrochloric acid washing solution is 1.2 to 2.0 mol / L, and the concentration of the second hydrochloric acid washing solution is 0.4 to 1.0 mol / L.

[0011] Further, in step S1, the concentration of the first hydrochloric acid washing solution is 2.0 mol / L, and the concentration of the second hydrochloric acid washing solution is 1.0 mol / L, and each solution is used for washing once.

[0012] Furthermore, in step S1, the ratio of Ti3AlC2, LiF, and HCl solution is 1.0 g: 1.2 g: 30 mL; the concentration of the HCl solution is 12 mol / L.

[0013] Furthermore, in step S1, the etching temperature is 35–50 °C, preferably 45 °C, and the etching time is 24–36 h, preferably 36 h.

[0014] Furthermore, in step S1, Ti3AlC2 is added to the etching solution in small amounts and batches for etching, with the time interval between two adjacent additions being 0.5 to 2 minutes.

[0015] Furthermore, in step S2, the operation of adding deionized water to the precipitate and performing vortex redispersion and centrifugation in sequence is carried out 2 to 5 times, with a centrifugation speed of 10,000 rpm and a centrifugation time of 15 min.

[0016] Furthermore, in step S3, the vortexing and centrifugation cycles are repeated 3 to 5 times; after each centrifugation, no solid-liquid separation is performed, no deionized water is added, and the supernatant and precipitate are vortexed and dispersed again before centrifugation; the vortexing speed is 1000 to 2000 rpm, and the vortexing time is 10 to 20 min; the centrifugation speed is 10000 rpm, and the centrifugation time is 15 min.

[0017] Furthermore, in step S3, the inert atmosphere is nitrogen or argon, the ice bath ultrasonic temperature is 0–10 °C, and the ultrasonic time is 30–120 min.

[0018] Furthermore, in step S4, the centrifugation speed is 3500 rpm, and the centrifugation time is 10 min; the vortex speed is 1000 rpm, and the vortexing time is 5 min.

[0019] (ii) The present invention also provides a high concentration of Ti3C2T x MXene colloid, prepared by the method described above, wherein the Ti3C2T x The mass concentration of MXene colloid is not less than 10 mg / mL.

[0020] (iii) The present invention also provides the high-concentration Ti3C2T described above. x Applications of MXene colloids in the preparation of tribological additives, energy storage materials, electromagnetic shielding materials, sensing materials, conductive coatings, or catalytic materials.

[0021] The beneficial effects of this invention are: (1) The present invention sets a hydrochloric acid washing step with decreasing concentration between the etching mother liquor and the deionized water washing. By gradually replacing the high acidity etching mother liquor remaining in the precipitate, the free acid load and soluble ion load of the system can be reduced in advance, thereby reducing the number of subsequent deionized water washings and reducing the risk of system dilution and sheet oxidation caused by repeated washing. (2) Based on the pH of the supernatant and the stable state of the black dispersed phase, this invention distinguishes between the acid removal and impurity removal stage and the colloidal recovery stage, and reduces the effective Ti3C2T by means of circulating vortexing, centrifugation and sediment recycling extraction. x This reduces the loss of film due to discharge with the washing liquid or retention in the sediment, and improves the film recovery rate and colloidal dispersion uniformity. (3) This invention combines inert atmosphere ice bath ultrasound and centrifugal fractionation to promote the formation of Ti3C2T x While dissociating layered particles, oxidation and excessive fragmentation are inhibited, allowing for the direct acquisition of high-concentration Ti3C2T without secondary concentration operations such as evaporation concentration, flocculation concentration, or high-speed sedimentation followed by small-volume water re-dispersion. xMXene colloids are prepared using a simple process that facilitates large-scale production. Attached Figure Description Figure 1 The Ti3AlC2 precursor and the Ti3C2T obtained in Example 1 of this invention x XRD patterns of MXene; Figure 2 The multilayer Ti3C2T obtained in Embodiment 1 of the present invention x SEM topography of MXene; Figure 3 The Ti3C2T obtained in Example 1 of this invention x TEM image of MXene; Figure 4 The Ti3C2T obtained in Example 1 of this invention x HRTEM lattice fringes of MXene; Figure 5 The Ti3C2T obtained in Example 1 of this invention x AFM 3D profile of MXene sheets; Figure 6 The Ti3C2T obtained in Example 1 of this invention x AFM two-dimensional height topography of MXene sheets; Figure 7 The Ti3C2T obtained in Example 1 of this invention x AFM height profile of MXene sheets; Figure 8 This invention relates to a high-concentration Ti3C2T x A schematic diagram of the MXene colloid preparation method. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some, but not all, embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0023] This invention provides a high concentration of Ti3C2T x The method for preparing MXene colloids includes the following steps: Step S1: LiF was mixed with HCl solution (concentration 12 mol / L) and magnetically stirred at 550 rpm for 0.5 h at room temperature. The reaction temperature was then raised to 35–50 °C and stirring continued for another 0.5 h to obtain the etching solution. Ti3AlC2 was added in small batches to the etching solution for etching, with a 1-minute interval between each addition. After addition, the mixture was reacted at 35–50 °C with continuous stirring for 24–36 h to obtain Ti3C2T containing multiple layers. x Etching paste containing products, residual acid, and soluble byproducts; The etching slurry is centrifuged to remove the mother etching solution. The precipitate is then washed with a first hydrochloric acid washing solution of 1.2–2.0 mol / L, centrifuged again, and the precipitate is collected. Next, the precipitate treated with the first hydrochloric acid washing solution is washed with a second hydrochloric acid washing solution of 0.4–1.0 mol / L, centrifuged again, and the precipitate is collected. The ratio of Ti3AlC2, LiF, and HCl solution used is 1.0 g:1.2 g:30 mL. This invention reduces the free acid load and ionic strength of the system by gradually replacing the residual high-acidity mother etching solution in the precipitate with hydrochloric acid washing solutions of decreasing concentration, and also removes soluble species containing Li, Al, or F and other etching byproducts beforehand.

[0024] Step S2: Add water to the precipitate obtained in Step S1, and use vortexing to fully and uniformly redisperse the precipitate. Then centrifuge at 10,000 rpm for 15 min to obtain the supernatant and precipitate. Measure the pH of the obtained supernatant. Add water again to the precipitate obtained from the first centrifugation, vortex redisperse, and centrifuge again to obtain the supernatant and precipitate after a second centrifugation. Measure the pH of the obtained supernatant. Perform the above water addition, vortex redispersion, and centrifugation operations 2-5 times. If the supernatant pH is ≤6 or does not show a stable, uniform black dispersion after centrifugation, discard the supernatant. If the supernatant pH is >6 and still shows a stable, uniform black dispersion after centrifugation, retain the supernatant to obtain a black neutral dispersion, in order to recover Ti3C2T that has entered a colloidal dispersion state. x Layers.

[0025] Step S3: The stable black dispersion obtained in step S2 is vortexed at 1000–2000 rpm for 10–20 min, followed by centrifugation at 10000 rpm for 15 min. This vortexing and centrifugation process is repeated 3–5 times. After each centrifugation, the supernatant is not removed, the sediment is not discarded, and deionized water is not added. Instead, the supernatant and precipitate in the centrifuge tube are vortexed again as a whole, so that the sediment formed by centrifugation is uniformly dispersed in the original dispersion medium. The periodic shearing, liquid-solid interface disturbance, and relative motion between particles generated by the vortex flow field can promote the dispersion of Ti3C2T. xThe layered particles are continuously loosened, improving their dispersion uniformity. After vortexing and centrifugation, the supernatant and precipitate are re-vortexed and then ultrasonically treated for 30–120 min under an inert atmosphere and an ice bath at 0–10 °C. Preferably, the gas phase in the reaction vessel is replaced with an inert gas before ultrasonic treatment, or an inert gas is continuously introduced into the dispersion or the space above it during ultrasonic treatment. The local shearing and microjets generated by ultrasonic cavitation can promote the dispersion of Ti3C2T. x The layered particles further dissociate, refining the lateral dimensions of the resulting lamellars. Intermittent ultrasonic treatment can be used to reduce ultrasonic heating and mitigate lamellar oxidation and excessive fragmentation caused by continuous cavitation. After ultrasonic treatment, Ti3C2T is obtained. x Nanosheet colloidal dispersion.

[0026] Step S4: Take the Ti3C2T obtained in step S3 x Centrifugation was performed on the colloidal dispersion of nanosheets to allow incompletely separated multilayered particles and coarse aggregates to settle. The upper black colloidal dispersion was collected and retained. An appropriate amount of deionized water was added to the resulting black sediment after centrifugation, and the mixture was vortexed to ensure that Ti3C2T particles remained dispersed within the sediment. x The lamellae were re-released into the liquid phase. After vortexing, the supernatant was centrifuged again and the resulting black colloidal dispersion was collected. The above operation of "redispersing sediment with water - vortexing - centrifugation - collecting supernatant" was repeated until the color of the supernatant after centrifugation became significantly lighter. The black colloidal dispersions obtained from each round were combined to obtain Ti3C2T with a mass concentration of not less than 10 mg / mL. x MXene colloidal dispersion. Centrifugation speed was 3500 rpm, and the centrifugation time was 10 min per centrifugation; vortexing speed was 1000 rpm, and the vortexing time was 5 min per vortex.

[0027] This invention reduces the residual acid and soluble ion load carried by the etching product by unloading the acid load in step S1, thereby reducing the number of deionized water washing steps required in step S2. Through the identification and retention of the stable black neutral dispersed phase in step S2, the enhanced dispersion by cyclic vortex-centrifugation in step S3, and the cyclic extraction of dispersible lamellae in the black deposit in step S4, the Ti3C2T content is reduced. x The loss of effective film layers during washing, peeling, and fractionation processes was minimized. Simultaneously, by controlling the amount of deionized water added in each round, the number of extraction cycles, and the final colloid volume, Ti3C2T with a mass concentration of not less than 10 mg / mL was directly obtained without employing secondary concentration operations such as evaporation concentration, concentration with added flocculants, or high-speed centrifugation and redispersing of all film layers with a small amount of water after colloid formation. x MXene colloidal dispersion.

[0028] The core technology of this invention lies in combining decreasing acidity replacement, colloidal phase identification, retention of stable neutral dispersed phase, enhanced dispersion through cyclic vortexing, low-temperature ultrasonication in an inert atmosphere, and cyclic extraction of sediments to form a continuous process chain. The initial stage uses an acidic environment to pre-unload residual acid and soluble ion loads; the middle stage retains and enhances the dissociation of the dispersed phase after the formation of stable colloids; and the final stage recovers still-dispersible effective lamellae from the sediments through cyclic extraction. Ultimately, this achieves the effects of reducing the number of water washes, increasing lamellae recovery rate, and directly obtaining high-concentration colloids.

[0029] Example 1 This embodiment provides a high-concentration Ti3C2T x The method for preparing MXene colloids includes the following steps: (1) Preparation of etching solution: In a fume hood, 12.0 g of lithium fluoride was slowly added to 300 mL of HCl solution with a concentration of 12 mol / L. The solution was magnetically stirred at 550 rpm for 0.5 h at room temperature. Then the reaction system was heated to 45 °C and stirred for 30 min to fully disperse the lithium fluoride and obtain the LiF / HCl etching solution.

[0030] (2) Etching Ti3AlC2: Weigh 10.0 g of Ti3AlC2 and add it to the etching solution in two portions for etching. The time interval between the two additions is 1 min. After the Ti3AlC2 addition is complete, continue stirring and reacting at 45 ℃ and 550 rpm for 36 h to obtain Ti3C2 containing multiple layers. x Etching paste containing products, residual acid, and soluble byproducts.

[0031] (3) Pickling: Dispense the etching slurry obtained in step (2) into centrifuge tubes, each tube containing 25-30 mL of liquid, centrifuge at 10000 rpm for 15 min, and discard the mother etching solution; Add 25 mL of 2.0 mol / L hydrochloric acid washing solution to each centrifuge tube, vortex to fully redisperse the precipitate, and then centrifuge at 10,000 rpm for 15 min, discarding the supernatant. Then add 25 mL of 1.0 mol / L hydrochloric acid washing solution to each centrifuge tube, and repeat the vortex redispersion and centrifugation process, discarding the supernatant.

[0032] (4) Vortex-assisted washing and colloidal recovery: Add deionized water to the precipitates obtained in step (3), and use vortex oscillation to fully and uniformly redisperse the precipitates. Then centrifuge at 10,000 rpm for 15 min to obtain the supernatant and precipitate. Measure the pH of the obtained supernatant. Add water again to the precipitate obtained from the first centrifugation, vortex redisperse, and centrifuge to obtain the supernatant and precipitate after the second centrifugation. Measure the pH of the obtained supernatant. Perform the above water addition, vortex redispersion, and centrifugation operations for a total of 4 rounds. If the supernatant pH ≤ 6 or does not show a stable and uniform black dispersion state after centrifugation, discard the supernatant. If the supernatant pH > 6 and still shows a stable and uniform black dispersion state after centrifugation, retain the supernatant to obtain a black neutral dispersion to recover Ti3C2T that has entered the colloidal dispersion state. x Layers.

[0033] (5) Enhanced dispersion by vortexing and centrifugation: The black neutral dispersion obtained in step (4) was vortexed at 2000 rpm for 15 min, and then centrifuged at 10000 rpm for 15 min. After centrifugation, the supernatant was not removed, the sediment was not discarded, and deionized water was not added. Instead, the supernatant and precipitate in the centrifuge tube were vortexed again as a whole to redisperse the sediment in the original dispersion medium. The above centrifugation-vortexing operation was repeated 4 times to obtain Ti3C2T. x Black neutral dispersion.

[0034] (6) Ice bath ultrasonic dissociation: The Ti3C2T obtained in step (5) x The stable black dispersion was placed in an ice bath at 4 °C, the air inside the container was replaced with nitrogen, and the mixture was ultrasonically treated for 90 min under nitrogen protection. The local shearing and microjets generated by ultrasonic cavitation promoted the growth of Ti3C2T. x The layered particles further dissociate, refining the lateral dimensions of the resulting lamellars. Nitrogen protection reduces contact between oxygen and the lamellars, while an ice bath suppresses the temperature rise caused by ultrasound, thus reducing the risk of lamellar oxidation and excessive fragmentation. After ultrasonic treatment, Ti3C2T is obtained. x Nanosheet colloidal dispersion.

[0035] (7) Take the Ti3C2T obtained in step (6) x The nanosheet colloidal dispersion was centrifuged at 3500 rpm for 10 min to allow incompletely separated multilayer particles and coarse aggregates to settle. The upper black colloidal dispersion was collected and retained. Deionized water was added to the black sediment obtained after centrifugation, and the mixture was vortexed at 1000 rpm for 5 min to allow Ti3C2T particles with dispersibility to remain in the sediment. xThe lamellae were re-released into the liquid phase. After vortexing, the mixture was centrifuged again at 3500 rpm for 10 min, and the resulting upper black colloidal dispersion was collected. The above operation of "redispersing sediment with water - vortexing - centrifugation - collecting upper colloid" was repeated until the color of the supernatant after centrifugation became significantly lighter. The upper black colloidal dispersions obtained from each round were combined to obtain Ti3C2T. x MXene colloidal dispersion.

[0036] The Ti3C2T obtained in Example 1 was determined by fixed-volume sampling and drying weighing method. x The mass concentration of the MXene colloidal dispersion is approximately 12.5 mg / mL.

[0037] The product obtained in Example 1 was characterized in terms of structure and morphology. See [link to relevant documentation]. Figures 1-7 .

[0038] X-ray diffraction results showed that, compared with the Ti3AlC2 precursor, the Ti3C2T obtained in Example 1... x The main characteristic peaks of Ti3AlC2 were significantly weakened or disappeared, and Ti3C2T x The (002) diffraction peak shifted to lower angles and broadened, indicating that the Al layer was effectively removed and the interlayer spacing increased. Scanning electron microscopy results showed that the etching product exhibited a distinct layered open structure. Transmission electron microscopy results showed that the obtained Ti3C2T x It exhibits a two-dimensional lamellar morphology and relatively intact lamellar edges. Atomic force microscopy results show that the obtained colloid contains monolayers and / or few layers of Ti3C2T. x Layers.

[0039] Example 2 This embodiment provides a high-concentration Ti3C2T x The method for preparing MXene colloids differs from that in Example 1 in that: In step (3) of this embodiment, the concentration of the first hydrochloric acid washing solution is 1.2 mol / L, and the concentration of the second hydrochloric acid washing solution is 0.4 mol / L. Other steps and parameters are the same as in Example 1.

[0040] The Ti3C2T obtained in Example 2 was determined by fixed-volume sampling and drying weighing method. x The mass concentration of the MXene colloidal dispersion is approximately 12 mg / mL.

[0041] Example 3 This embodiment provides a high-concentration Ti3C2T x The method for preparing MXene colloids differs from that in Example 1 in that: In step (5) of this embodiment, a combination of low-shear mechanical stirring and tumbling mixing is used instead of vortex oscillation, so that the sediment formed by centrifugation is redispersed in the original dispersion medium. Other steps are the same as in embodiment 1.

[0042] After subsequent ice bath ultrasonication and cyclic centrifugation fractionation, the obtained product still possesses Ti3C2T x The layered structure and the single-layer and few-layer sheet characteristics indicate that the technical solution of the present invention does not depend on a specific type of vortex oscillation device.

[0043] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: In step (3), after centrifuging the etching slurry to remove the etching mother liquor, the first and second hydrochloric acid washing steps are omitted, and the process proceeds directly to step (4), where the precipitate is repeatedly washed with deionized water, vortexed redispersed and centrifuged until the pH of the supernatant is greater than 6.

[0044] Compared to Example 1, Comparative Example 1 requires more rounds of deionized water washing. Example 1 only requires 4 rounds of deionized water washing, while Comparative Example 1 requires more than 10 rounds. Furthermore, a black supernatant appears in the earlier washing stage, indicating that the removal process of residual acid and soluble byproducts is similar to that of Ti3C2T. x The colloidification process of the sheets overlaps.

[0045] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step (4), the supernatant treatment method is not switched according to the pH of the supernatant and the stable state of the black dispersed phase during the water washing process. Instead, all the supernatants obtained from each round of centrifugation are discarded, and only the final precipitate is subjected to cyclic vortexing, ultrasonication and centrifugal classification.

[0046] Step (4) of Comparative Example 2 is as follows: Add deionized water to the precipitates obtained in step (3), and vortex to fully and uniformly redisperse the precipitates. Centrifuge the dispersion at 10,000 rpm for 15 min, discard all supernatant after centrifugation, and retain the precipitate. Add deionized water to the precipitate again, and repeat the vortex redispersion, centrifugation (10,000 rpm, 15 min), and supernatant discarding operations. The above water addition-vortex redispersion-centrifugation-supernatant discarding operation is performed 4 times. After the 4th centrifugation, retain the final precipitate; add deionized water to the precipitate, and perform cyclic vortexing, ultrasonic treatment, and centrifugation classification in sequence to collect Ti3C2T that has entered the colloidal dispersion state. x The film is then processed to obtain a black neutral dispersion.

[0047] Ti3C2T obtained in Comparative Example 2 xThe total volume of the MXene colloidal dispersion was 700 mL, with a mass concentration of approximately 8.5 mg / mL, corresponding to Ti3C2T. x The solid recovery was approximately 5.95 g. The total volume of the colloidal dispersion obtained in Example 1 was also 700 mL, with a mass concentration of approximately 12.5 mg / mL, corresponding to Ti3C2T x The amount of solids recovered was approximately 8.75 g. Compared to Comparative Example 2, Example 1 recovered more Ti3C2T. x The amount of solids was approximately 2.80 g, and both the mass concentration and the amount of solids recovered increased by approximately 47.1%.

[0048] The above results indicate that if the entire supernatant is discarded after a stable and uniform black dispersed phase has formed (pH > 6), it will cause Ti3C2T, which has already entered a colloidal dispersion state, to be lost. x Effective layer loss.

[0049] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that: this comparative example uses conventional etching and direct water washing methods to prepare Ti3C2T. x After ultrasonic exfoliation, the dispersion was only subjected to low-speed centrifugation for classification, and the upper black dispersion was collected. Step-by-step hydrochloric acid washing, colloidal phase window recovery, and sediment recycling were not included.

[0050] Comparative Example 3 is as follows: The LiF / HCl etching solution was prepared according to steps (1) and (2) of Example 1, and 10.0 g of Ti3AlC2 was etched to obtain the etching slurry; The obtained etching slurry was dispensed into centrifuge tubes, 25 mL per tube, and centrifuged at 10,000 rpm for 15 min, discarding the mother etching solution. 25 mL of deionized water was added to each centrifuge tube, and the precipitate was vortexed to fully redisperse it. The precipitate was then centrifuged at 10,000 rpm for 15 min, and the supernatant was discarded. This process of adding water, redispersing, centrifuging, and discarding the supernatant was repeated until the pH of the supernatant after centrifugation was greater than 6, yielding the water-washed Ti3C2T. x Precipitation. The supernatant obtained during the washing process should be discarded. Ti3C2T after water washing x The same volume of deionized water as in Example 1 was added to the precipitate, and the precipitate was fully redispersed by vortexing. The resulting dispersion was placed in an ice bath at 4 °C, the air in the container was replaced with nitrogen, and the mixture was ultrasonically treated for 90 min under nitrogen protection to obtain a mixed dispersion containing monolayer / few-layer Ti3C2Tx nanosheets and incompletely exfoliated particles. The obtained Ti3C2T containing monolayer / few-layersx The mixture of nanosheets and incompletely exfoliated particles was centrifuged at 3500 rpm for 10 min to allow the incompletely exfoliated multilayer particles and coarse aggregates to settle. After centrifugation, only the upper black colloidal dispersion was collected once. No deionized water was added to the resulting sediment, and the sediment was not vortexed for redispersion or centrifuged again. Record the actual volume V3 of the obtained upper black colloidal dispersion, and determine its mass concentration C3 using the fixed-volume sampling-drying and weighing method. Comparative Example 3 recovers Ti3C2T x Solid mass was calculated as C3×V3. To eliminate the influence of colloid volume differences on the mass concentration comparison results, 700 mL was used as a uniform reference volume, based on the recovered Ti3C2T. x Solid mass calculation: Equal volume equivalent mass concentration for Comparative Example 3.

[0051] Comparative Example 3 represents a conventional preparation route where the etching product is directly washed with deionized water, ultrasonically stripped, and fractionated by a single low-speed centrifugation, followed by direct collection of the supernatant. This method lacks acid load cascading unloading and colloidal phase window recovery, and it does not address the still-dispersible Ti3C2T in the sediment obtained from low-speed centrifugation. x Layers are extracted cyclically.

[0052] Compared with Comparative Example 3, Example 1 reduced Ti3C2T by using stepped hydrochloric acid washing, colloidal phase window recovery, and sediment recycling. x Loss of the film during washing and centrifugation. Under the condition of the same Ti3AlC2 feed rate and converted to a uniform reference volume of 700 mL, the mass concentration of the colloidal dispersion obtained in Example 1 was 12.5 mg / mL, corresponding to Ti3C2T x The solid recovery was 8.75 g; the volumetric equivalent mass concentration of Comparative Example 3 was approximately 8.0 mg / mL, corresponding to Ti3C2T x The amount of solids recovered was approximately 5.60 g. Compared to Comparative Example 3, Example 1 recovered more Ti3C2T. x The solid content was approximately 3.15 g, and the volumetric mass concentration and solid recovery were both increased by approximately 56.3%.

[0053] The above embodiments and comparative examples demonstrate that the present invention, by setting a hydrochloric acid washing step with decreasing concentration, pre-reduces the residual acid and soluble ion load carried by the etching products, and distinguishes between the acid removal and impurity removal stage and the colloidal recovery stage based on the pH of the supernatant and the state of the black dispersed phase, thereby reducing the number of deionized water washes and effectively increasing the Ti3C2T content. xThe process reduces the risk of system dilution and lamellar oxidation caused by repeated washing by eliminating the loss of lamellar layers. Simultaneously, combining circulating vortexing, centrifugation, inert atmosphere ice bath ultrasonication, and sediment recycling extraction promotes the dissociation of lamellar particles, improves the effective lamellar recovery rate, and reduces the risk of oxidation and excessive fragmentation. This allows for the direct acquisition of high-concentration Ti3C2T without secondary concentration operations such as evaporation concentration, flocculation concentration, or high-speed sedimentation followed by small-volume water re-dispersion. x MXene colloid.

[0054] The above are merely preferred embodiments of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should be considered within the scope of protection of the present invention.

Claims

1. A high-concentration Ti3C2T x The method for preparing MXene colloids is characterized by, Includes the following steps: S1: Prepare an etching solution by mixing LiF with HCl solution, add Ti3AlC2 to the etching solution for etching, remove the mother etching solution by centrifugation, and wash the precipitate with at least two stages of dilute hydrochloric acid solution with concentrations from high to low. S2: Add deionized water to the precipitate obtained in step S1, and perform vortex redispersion and centrifugation treatment in sequence, repeating at least once; if the pH of the supernatant is ≤6 or it does not show a stable and uniform black dispersion state after centrifugation, discard the supernatant; if the pH of the supernatant is >6 and it still shows a stable and uniform black dispersion state after centrifugation, retain the supernatant to obtain a black dispersion. S3: The black dispersion obtained in step S2 is subjected to multiple rounds of vortexing and centrifugation, followed by ultrasonic treatment under an inert atmosphere and ice bath conditions to obtain Ti3C2T. x Nanosheet colloidal dispersion; S4: Take the Ti3C2T obtained in step S3 x The nanosheet colloidal dispersion was centrifuged, and the upper black colloidal dispersion was collected. The resulting precipitate was redispersed with water by vortexing and centrifugation again, and the upper black colloidal dispersion was collected. The process of redispersing the precipitate with water, centrifugation, and collecting the upper black colloidal dispersion was repeated, and the upper black colloidal dispersions obtained from each round were combined to obtain a monolayer of Ti3C2T. x MXene colloidal dispersion.

2. The high-concentration Ti3C2T according to claim 1 x The method for preparing MXene colloids is characterized by: In step S1, the etching mother liquor is removed by centrifugation, and the precipitate is washed sequentially with a first hydrochloric acid washing solution and a second hydrochloric acid washing solution with a concentration lower than that of the first hydrochloric acid washing solution. The first hydrochloric acid washing solution and the second hydrochloric acid washing solution are washed 1 to 2 times respectively. The concentration of the first hydrochloric acid washing solution is 1.2–2.0 mol / L, and the concentration of the second hydrochloric acid washing solution is 0.4–1.0 mol / L.

3. The high-concentration Ti3C2T according to claim 1 x The method for preparing MXene colloids is characterized by: In step S1, the ratio of Ti3AlC2, LiF and HCl solution used is 1.0 g: 1.2 g: 30 mL; The concentration of the HCl solution is 12 mol / L.

4. The high-concentration Ti3C2T according to claim 1 x The method for preparing MXene colloids is characterized by: In step S1, the etching temperature is 35–50 °C and the etching time is 24–36 h.

5. The high-concentration Ti3C2T according to claim 1 x The method for preparing MXene colloids is characterized by: In step S2, deionized water is added to the precipitate and vortex redispersion and centrifugation are performed in 2 to 5 rounds. The centrifugation speed is 10,000 rpm and the centrifugation time is 15 min.

6. The high-concentration Ti3C2T according to claim 1 x The method for preparing MXene colloids is characterized by: In step S3, the vortex and centrifugal treatment cycles are repeated 3 to 5 times. The vortex rotates at a speed of 1000–2000 rpm for 10–20 min; the centrifugation speed is 10000 rpm for 15 min.

7. The high-concentration Ti3C2T according to claim 1 x The method for preparing MXene colloids is characterized by: In step S3, the inert atmosphere is nitrogen or argon, the ice bath ultrasonic temperature is 0–10 °C, and the ultrasonic time is 30–120 min.

8. The high-concentration Ti3C2T according to claim 1 x The method for preparing MXene colloids is characterized by: In step S4, the centrifugation speed is 3500 rpm, and the centrifugation time is 10 min each time. The vortex rotates at 1000 rpm, and each vortex cycle lasts for 5 minutes.

9. A high-concentration Ti3C2T x MXene colloid, characterized in that: The Ti3C2T is prepared by the preparation method according to any one of claims 1 to 8. x The mass concentration of MXene colloid is not less than 10 mg / mL.

10. The high-concentration Ti3C2T as described in claim 9 x Applications of MXene colloids in the preparation of tribological additives, energy storage materials, electromagnetic shielding materials, sensing materials, conductive coatings, or catalytic materials.